Esplenectomia associa-se com disfunções sexuais e redução da libido em humanos - Kelly Renata Sabino (2020)
The functions of the spleen include blood clearance, hematopoiesis, metabolism, and immune response to antigens, in addition to producing amino acids, storing and controlling the release of metals. Removal of the spleen due to disease or trauma is followed by severe complications resulting from the asplenic state, comprising immune-deficiency, blood adverse conditions and metabolic disorders, dyslipidemias, among others, which can lead to an early death due to sepsis and pulmonary embolism, as well as hepatic and hematological diseases. Although some patients report a sexual disinterest that arises after a splenectomy, this characteristic of asplenia has not yet been studied. To verify the existence of changes in one´s libido and other sexual functions associated with the asplenic state. This study selected 30 men and 30 women, all of whom were adult and healthy, in the postoperative stage of the total splenectomy caused by splenic trauma over a period of more than one year. The Erectile Dysfunction Questionnaire was applied to the men, while the Sexual Dysfunction Questionnaire was applied to the women. The analysis compared the answers obtained regarding the periods before and after the splenectomy. All patients underwent laboratory exams with hematological and biochemical analyses, including sexual hormones. A reduction in the libido and an increase in sexual dysfunctions after the total splenectomy in both men and women, p < 0.001 were found. The postoperative laboratory exams presented normal values in both sexes. The asplenic state is associated with an accentuated reduction in libido and with intense sexual dysfunctions, both in men and women, with no changes in the hematological and biochemical laboratory exams, including hormones.